2017
DOI: 10.1002/ejp.1115
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of persistent post‐operative pain: Pain‐specific psychological variables compared with acute post‐operative pain and general psychological variables

Abstract: Our results suggest that pain-specific psychological variables such as pain anxiety and pain hypervigilance add significantly to the prediction of persistent post-operative pain and might even outperform established predictors such as acute pain and general psychological variables. Clinicians might benefit from the development of time-economic screening tools based on these variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…8 Higher levels of depressive symptoms 39,53,54 have also been associated with persistent pain after mastectomy, as has the number of antidepressants used. 56 Some have speculated that pain-related or painspecific variables (such as pain catastrophizing) may be more predictive than general psychological measures, 25 although we did not observe this. These various measures (anxiety, depression, distress, negative affect) are often moderately to strongly intercorrelated, raising the possibility that the one which is most predictive in the context of a multivariate regression may vary across samples, depending on several factors, such as the mean group score on those variables, and presence of other measured similar variables.…”
Section: Psychosocial Factors and Painmentioning
confidence: 53%
“…8 Higher levels of depressive symptoms 39,53,54 have also been associated with persistent pain after mastectomy, as has the number of antidepressants used. 56 Some have speculated that pain-related or painspecific variables (such as pain catastrophizing) may be more predictive than general psychological measures, 25 although we did not observe this. These various measures (anxiety, depression, distress, negative affect) are often moderately to strongly intercorrelated, raising the possibility that the one which is most predictive in the context of a multivariate regression may vary across samples, depending on several factors, such as the mean group score on those variables, and presence of other measured similar variables.…”
Section: Psychosocial Factors and Painmentioning
confidence: 53%
“…There are some limitations to the present study. Known risk factors of postoperative pain are female gender, lower age, preoperative pain, intraoperative factors and psychological factors, and so on [8,[19][20][21]. Furthermore, it was reported that psychological factors were correlated with venous cannulation-induced pain score [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations to the present study. Known risk factors of postoperative pain are female gender, lower age, preoperative pain, intraoperative factors and psychological factors, and so on [8,[19][20][21]. Furthermore, it was reported that psychological factors were correlated with venous cannulation-induced pain score [22].…”
Section: Discussionmentioning
confidence: 99%